Mobile-assisted Language Learning(MALL) Exploration: Implementation in Extensive Reading subject for English Education study Program: Eksplorasi Mobile-Assissted Language Learning (MALL): Implementasi dalam pembelajaran Extensive Reading kepada Mahasiswa Pendidikan Bahasa Inggris - Al Fath, Muhammad Sandy; Azis, Muhammad Abdul; Putri, Nikmah Sistia Eka; Setiani, Fatimah (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2023)
With the relatively low habit of reading, Indonesia created the urgent condition. The same problem actually happen in Universitas Muhammadiyah Sampit, especially in English educcation study program.Remebering how crucial reading in development of Language, the concrete way out deriving the will of reading of students is needed. One of the way out in UMSA bring the bright perspectively in both side, even students and lecturer in the class. This study aims to find out Description of Using MALL in the instructional process. The focus of this study is the extensive reading lecture in English Education Study Program in UMSA. The researchers use a type of qualitative research which is Case Study. Then, the instruments of this study were Interview and Documentation. Primary data were collected merely through interview; however, it has been taken deeply on the collecting data. The secondary data in this study are sources related to the problems in the object of this paper. The implementation of the MALL in this study was using Wattpad mobile apps as teaching media. Findings consists of the use, the features and the assessment of Wattpad as the learning medium in the class. The reason the supporting lecturer chose to use Wattpad was based on the needs of students in the Extensive Reading class. With Wattpad students can explore various uploaded literary works concluding on building and creating reading materials independently. In addition, students can collaborate with other students in building their knowledge and solving problems together.